Optimizing nitrogen use efficiency of six forage grasses to reduce nitrogen loss from intensification of tropical pastures - Bastidas, Mike; Vázquez, Eduardo; Villegas, Daniel Mauricio; Rao, Idupulapati M.; Gutierrez, Jhon Freddy; Vivas Quila, Nelson José; Amado, Miguel; Berdugo, Carlos; Arango, Jacobo (Elsevier, 2024)
We aimed to evaluate the effect of different types and rates of nitrogen (N) fertilizers on plant biomass production, nitrogen use efficiency (NUE), and nitrous oxide (N2O) emissions of six tropical forage grass cultivars. This field study was conducted in Colombia under tropical conditions in two phases. Phase 1: we evaluated the effect of different types of N fertilizers (urea; calcium ammonium nitrate (CAN); and urea-ammonium sulfate (U-AS) using a single dose of application of 25 kg N ha−1 cut−1, along with a control treatment for each grass without application of fertilizer) on forage dry matter, crude protein, N uptake, N surplus, and NUE. The study focused on six tropical forage grass cultivars: Urochloa humidicola cv. Tully, U. hybrid cv. Cobra, U. hybrid cv. Cayman, Megathyrsus maximus cv. Mombasa, Cynodon nlemfuensis cv. Stargrass and U. decumbens cv. Basilisk. We found that the biomass production and protein content of each forage grass cultivar responded differently to different N fertilizer types. In consequence, the NUE of each forage grass cultivar was strongly affected by the type of N fertilizer applied. For example, Cayman showed a NUE of 87.8% with CAN and 40.4% with urea, while the NUE of Basilisk with CAN was 8.0% and 76.4% with urea. Maximum NUE values were obtained for Stargrass and Cayman with CAN (91.7 and 87.8%, respectively) and for Mombasa with urea (89.9%). Phase 2: we selected three combinations of forage grass cultivars and type of N fertilizer, and we evaluated the impact of four rates of N application (0, 10, 20, and 30 kg N ha−1 cut−1) on forage production and N2O emissions upon fertilization. In general, higher N fertilization rates increased the accumulated N2O emissions. However, we observed that the fertilization of Stargrass and Cayman grass with a rate of 20 kg N−1 cut−1 and Mombasa grass with a rate of 30 kg N−1 cut−1 were more beneficial than the other rates of N fertilization based on the biomass production and amount of N2O emitted are considered. This study highlights the importance of optimizing NUE in tropical pasture systems using an appropriate design of N fertilization strategy. Inappropriate N fertilizer use can significantly increase the N losses (e.g., through N2O emissions, with a potential contribution from N leaching). These findings provide valuable information for sustainable intensification of productive tropical livestock systems to spare land for other uses.